2012
DOI: 10.3892/or.2012.1737
|View full text |Cite
|
Sign up to set email alerts
|

Implications of cleaved caspase 3 and AIF expression in colorectal cancer based on patient age

Abstract: Abstract.A high incidence of colorectal cancer (CRC) has been established in the elderly population. Apoptosis is a key event in maintaining colon homeostasis, both in aging as well as in cancer prevention. Here, we report that colon morphology is affected during the aging process: crypt loss (P=0.045) and increasing distances between crypts (P=0.0001678) were observed, associated with a tendency for mucosa reduction (P=0.083). In addition, our results show that apoptosis plays a determining role on the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Caspase-3, the most critical apoptosis performer downstream of the caspase cascade, is known as the "death protease" (31). Previous studies have demonstrated that co-expression level of cleaved caspase-3 (cle-caspase-3) and caspase-3 might be a prognostic biomarker for cancer patients (32,33). This study demonstrates that QFG increased the expression of cle-caspase-3 in CRC tumor cells and induced apoptosis.…”
Section: Discussionmentioning
confidence: 54%
“…Caspase-3, the most critical apoptosis performer downstream of the caspase cascade, is known as the "death protease" (31). Previous studies have demonstrated that co-expression level of cleaved caspase-3 (cle-caspase-3) and caspase-3 might be a prognostic biomarker for cancer patients (32,33). This study demonstrates that QFG increased the expression of cle-caspase-3 in CRC tumor cells and induced apoptosis.…”
Section: Discussionmentioning
confidence: 54%
“…In this study, we found that treatments with FBR and is strongly associated with prolonged survival in male CRC patients [60]. Activated Casp3, which performs the cleavage of the poly (ADP-ribose) polymerase family, member 1 (PARP1) and induces cell apoptosis, is a useful strategy in colon cancer prevention and treatment [61]. In this study, we found that the dietary MCG-PC treatment significantly enhanced the activation of Casp3 in the colon tissue of CRC mice.…”
Section: Discussionmentioning
confidence: 91%
“…A total of 12 patients (men from 70 to 88 years old), who underwent CRC resection at Limoges University Hospital (France) between March 2011 and April 2014, were enrolled in this retrospective study, according to the Declaration of Helsinki. Exclusion criteria were applied as described before . Tissue collection was approved by the local ethics committee (‘Comité de Protection des Personnes, Sud Ouest Outre Mer’; CPP SOOM4; number DC‐2008‐604).…”
Section: Methodsmentioning
confidence: 99%